Catalytic hydrogenation of carboxylic acids using low-valent and high-valent metal complexes. Issue 95 (12th October 2018) - Yoshioka, Shota; Saito, Susumu
Abstract : Carboxylic acids are ubiquitous in bio-renewable and petrochemical sources of carbon. Abstract : Carboxylic acids are ubiquitous in bio-renewable and petrochemical sources of carbon. The hydrogenation of carboxylic acids to alcohols generates water as the only by-product, and thus represents a sustainable method for the production of these alternative energy carriers/platform chemicals on a large scale. Herein, we offer a brief account of the development of this new concept and molecular insights into cationic mononuclear low- and high-valent transition-metal complexes for the hydrogenation of carboxylic acids.